Carotid Cavernous Fistula - Neli Salsabila; Rani Himayani (Majority, 2020)
Carotid cavernous fistula (CCF) is an abnormal communication between arteries and veins within the cavernous sinus. The most common (70%-90%) etiology of CCF is trauma and spontaneus CCF (30%) due to aneurysms or the presence of atherosclerotic arteries. Various symptoms can be found in cases of CCF such as conjunctival chemosis, proptosis, pulsating exophthalmus, diplopia, ophthalmoplegia, orbital pain, bruits and blindness. Sometimes spontaneous CCF is misdiagnosed as conjunctivitis or late in diagnosis. Cranial nerve damage and vision loss in CCF can become permanent if left untreated. Therefore, this paper aims to find out cases of CCF, from the history and physical examination so that if the diagnosis of CCF has been established in ophthalmologist, it will be referred to the neurosurgery for further management. The history for the etiology of CCF and ophthalmological examination to see the symptoms and signs in CCF cases, and the diagnosis can also be confirmed by radiological examination computed tomography scan (CT Scan) and cerebral angiography as the gold standard. Management of CCF in ophthalmologist with medical therapy or surgery if an increased intraocular pressure is obtained and the management of symptoms in the eye. Based on the patients’s symptoms, treatment can be observation, neuro-radiological intervention, or neurosurgical intervention.